Clinical impact of defibrillation testing in a real‐world S‐ICD population: Data from the ELISIR registry. (18th December 2020) - Ricciardi, Danilo; Ziacchi, Matteo; Gasperetti, Alessio; Schiavone, Marco; Picarelli, Francesco; Diemberger, Igor; Bontempi, Luca; Di Belardino, Natale; Bisignani, Giovanni; De Bonis, Silvia; Mitacchione, Gianfranco; Calabrese, Vito; et al.
Abstract: Background: Current guidelines recommend defibrillation testing (DT) performance in patients with a subcutaneous implantable cardioverter defibrillator (S‐ICD), theoretically to reduce the amount of ineffective shocks. DT, however, has been proven unnecessary in transvenous ICD and real‐world data show a growing trend in avoidance of DT after S‐ICD implantation. Methods: All patients undergoing S‐ICD implant at nine associated Italian centers joining in the ELISIR registry (ClinicalTrials.gov Identifier: NCT04373876) were enrolled and classified upon DT performance. Long‐term follow‐up events were recorded and compared to report the long‐term efficacy and safety of S‐ICD implantations without DT in a real‐world setting. Results: A total of 420 patients (54.0 ± 15.5 years, 80.0% male) were enrolled in the study. A DT was performed in 254 (60.5%) patients (DT+ group), while in 166 (39.5%) was avoided (DT− group). Over a median follow‐up of 19 (11–31) months, a very low rate (0.7%) of ineffective shocks was observed, and no significant differences in the primary combined arrhythmic outcome were observed between the two groups ( p  = .656). At regression analysis, the only clinical predictor associated with the primary combined outcome was S‐ICD placement for primary prevention (odds ratio: 0.42; p  = .013); DT performance instead was not associated with a reduction in primary outcome ( p  = .375). Conclusion: Implanting an S‐ICD without DT does not appear to impact the safety of defibrillation therapy and overall patients' survival.